Bioactive Restorative Systems and Self-Adhesive Bonding: Assessing Long-Term Durability and Effectiveness in Dentin Adhesion - ELSAYED, ATEF EID MADKOUR; Almagasslah , Heba Jaffer Hussain; Abbas , Maram Turki Ahmed; khawajah , Rayan abduallah; alhindi, Razan radwan (Journal of Ecohumanism, 2024)
Background: Bioactive, ion-releasing restorative materials have emerged as a promising solution for improving dentin adhesion and long-term restoration durability. Self-adhesive materials simplify bonding procedures by eliminating the need for pre-treatment adhesives, potentially enhancing clinical outcomes. This study aimed to evaluate the microshear bond strength (µSBS) and interfacial micromorphology of contemporary bioactive restorative systems bonded to dentin. Methods: Eighty freshly extracted human molars were prepared and divided into four groups based on restorative material: Surefil One (self-adhesive bulk-fill composite), Cention Forte (alkasite-based material) with and without primer, and Fuji II LC (resin-modified glass ionomer, control). Specimens underwent immediate (24-hour) and delayed (6-month artificial saliva storage) µSBS testing using a universal testing machine. Failure modes were analyzed with stereomicroscopy, and scanning electron microscopy (SEM) was used to assess the restoration-dentin interface. Results: Cention Forte with primer exhibited the highest immediate and delayed µSBS values, significantly outperforming all other materials (p < 0.05). Surefil One and Cention Forte without primer showed the weakest bond strength, with a high incidence of adhesive failure and pre-test failures after aging. SEM analysis revealed superior interfacial adaptation in Cention Forte with primer and Fuji II LC, while Surefil One and Cention Forte without primer demonstrated poor dentin infiltration, interfacial gaps, and lack of resin tag formation. Conclusion: The results indicate that the use of a primer significantly enhances the bonding performance of alkasite-based materials, making them a viable alternative to resin-modified glass ionomers. However, self-adhesive bulk-fill composites and alkasite-based materials without primer exhibit weak adhesion to dentin, limiting their clinical applicability. Further research is needed to optimize self-adhesive restorative materials for improved long-term bonding efficacy.